Pilihan Terapi Infeksi Covid-19 Pada Anak - Joko Tri Atmojo; Rejo Rejo; Dewi Arradini; Aquartuti Tri Darmayanti; Aris Widiyanto (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: Not all Covid-19 infections in children are mild and show a good prognosis, so it is very important to define them as a vulnerable population. Information related to the treatment of Covid-19 infection in children is still very limited, so the authors are interested in conducting a systematic review to discuss and provide information related to various types of drugs and treatment of Covid-19 infection in children. Methods: A systematic database search was carried out in July 2020 through the PUBMED and Google Scholar databases. Keywords used include: "children and COVID-19" and "COVID-19 in children and treatment" and "Covid-19 in children and management". Results: The results of the collection of articles were 7 articles that showed various alternative therapies for Covid-19 in children, including traditional Chinese medicine, providing antivirus, giving RNA inhibitors, giving supportive therapy in the form of oxygen. The principle of treatment or treatment in children must follow the symptoms caused by minimizing the administration of antiviral drugs. Conclusion: Supportive therapy is still an option, in the country of origin of the SARS-CoV2 virus, namely Cina, the principles of traditional medicine are widely used in children compared to medical treatment in the form of providing antivirals, because previous studies did not show high effectiveness of antivirals in children.